Robust μ-Controller for Hydraulic Spool Valve, Pilot Operated with Switching Micro Valves - Jordan Kralev (Energies, 2021)
Hydraulic spool valve, pilot operated with bi-state switching micro valves is a low-cost alternative to the conventional proportional and high-response valves. However, high-frequency switching causes variations in the control flow which limits achievable spool tracking error. This paper presents the design of a robust <semantics>μ</semantics>-controller for the spool position reference tracking synthesized with D-K iterative procedure. Furthermore, in order to reduce wind-up effects in the closed-loop, the <semantics>μ</semantics>-controller is decomposed to a canonical observer and state feedback components which allows explicit introduction of the saturated control signal in the controller equations. The uncertainty model required for the <semantics>μ</semantics>-synthesis is inferred from the nonlinear hydraulic model by identification of a Box–Jenkins model set characterized by its parameter covariance matrix. The regulator is implemented in a 32-bit programmable logic controller (PLC) and its performance is experimentally verified on a laboratory test bench of electro-hydraulic power steering system.